Peningkatan Kapasitas Ibu Hamil Melalui Buku KIA Kelas Ibu Hamil Tahun 2024 - Yuniarti; Zakiah; Hapisah; Fitria Jannatul Laili; Efi Kristiana; Suryanti; Riska; Runa Helmina; Rusmia Azizah (Rena Cipta Mandiri, 2024)
Health development programs in Indonesia are currently prioritized towards improving the health status of mothers and children, particularly in the most vulnerable groups such as pregnant women, mothers giving birth, perinatal infants, toddlers, and women of reproductive age. In response to this, a community service activity titled